The Risk Factors Affecting Blood Transfusion in Patients Undergoing Coronary Artery Bypass Graft Procedure Related to Gender - SH Ahmadi; F Mehrany; M Abbaszadeh; E Jazayeri Gharebagh (Tehran University of Medical Sciences, 2010)
Background and Aim: Females were reported to have significantly lower hematocrit (Hct), which might be the cause of increased need for blood transfusion. The goal of this study is to determine risk factors affecting blood transfusion in patients undergoing coronary artery bypass graft procedure related to gender. Materials and Methods: A cross sectional review of 500 (306 males and 194 females) ASA physical status I or Il patients undergoing bypass procedures with saphenous vein graft performed over a one year period were included in this study. The conducting of anesthesia was standardized. For each patient, we recorded the gender, age, body weight, height, body surface area (BSA), and duration of surgery. Hematocrit levels prior to surgery and the end of surgery were recorded. Packed red blood cell (PRBC) administration and use of fresh frozen plasma (FFP) and platelets were noted. Differences between the data for female and male patients were evaluated using Student's t-test, Chi-square test and using regression analysis.Results: Approximately 57.2 % (111) female and only 39.9% (121) male patients received PRBCs. On average, females received 1. 6 units of PRBCs intraoperatively and 2. 6 units of PRBCs during the entire hospital stay, while the males received 1.1 units and 1.8 units for similar periods (P=0.0001). When females and males were compared within the same subgroups for age, body surface area (BSA), duration of surgery, and preoperative Hct, etc. ...had a significant correlation with age, postoperative Hct and BSA in females but had a significant correlation with preoperative Hct, preoperative PRBC and duration of surgery in males (P<0.05). Multiple logistic regression analysis showed that the probability of a patient receiving or not receiving PRBC transfusion is significantly influenced by preoperative Hct, postoperative Hct, duration of surgery, preoperative PRBC mass, and gender. Discussion and Conclusion: Gender is an independent essential determinant of blood transfusion in CABG patients, and may interact with BSA, preoperative Hct, duration of surgery and other factors in determining the probability of transfusion.